Fiqh Siyasah Examination of the Dynamics of Implementation of Presidential Regulations on Covid-19 Vaccination in Pelalawan Regency, Riau - Ferdi Yufriadi; Fadilla Syahriani (Al-Qisthu, 2023)
The COVID-19 vaccination program in Indonesia experiences various dynamics depending on the socio-cultural conditions of each region, and within this context, dynamics in urban areas are crucial as they represent the acceptance, understanding, and implementation of vaccination within a diverse and multicultural society. This research aims to examine how beliefs, social and economic conditions, and the role of religious institutions influence the urban community's acceptance of the COVID-19 vaccination program scheduled by the central government and implemented by local authorities. This study is a field research conducted in Pangkalan Kerinci Sub-district, Pelalawan Regency, Riau, Indonesia. Data were collected through interviews, observations, and documentation. The study indicates that the implementation of vaccination by local authorities reflects a harmonization between religious principles, public policies, and the socio-economic conditions of the community. This highlights the importance of health policies being aligned with the ethical foundations and religious principles embraced by the local community, which can serve as a strategy to address common challenges encountered in vaccination efforts across various locations.